2023
DOI: 10.1101/2023.07.05.547833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural signatures of natural behavior in socializing macaques

Abstract: Our understanding of the neurobiology of primate behavior largely derives from artificial tasks in highly-controlled laboratory settings, overlooking most natural behaviors primate brains evolved to produce1. In particular, how primates navigate the multidimensional social relationships that structure daily life and shape survival and reproductive success remains largely unexplored at the single neuron level. Here, we combine ethological analysis with new wireless recording technologies to uncover neural signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Some recent work has begun to unravel the neural processes that occur during free movement. 16 18 , 54 Our work builds on this past work in several ways. First, we were able to measure neural correlates of actions in an animal with a richer behavioral repertoire (59 distinct actions).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some recent work has begun to unravel the neural processes that occur during free movement. 16 18 , 54 Our work builds on this past work in several ways. First, we were able to measure neural correlates of actions in an animal with a richer behavioral repertoire (59 distinct actions).…”
Section: Discussionmentioning
confidence: 98%
“…Currently, constructing an ethogram requires the delineation of ethogrammatical categories, which involves the time-consuming and careful annotation of behavior by highly trained human observers. 54 Human-led ethogramming is slow, extremely costly, error prone, and susceptible to characteristic biases. 61 64 For these reasons, it is simply impractical for even moderately large datasets, collected either in an open environment or in the home cage.…”
Section: Discussionmentioning
confidence: 99%
“…Perspectives on the neural basis of primate behavior are evolving in hand with the increased use of ethological paradigms 22,26,28,34,35 and particularly as effects in conventional tasks are not necessarily recapitulated in the presumptive analogous natural behaviors 15,32 . Our results here showed that -while functional clusters of these processes are evident in the prefrontal and premotor cortices of marmosets engaged in natural vocal interactions -the organization is widely distributed throughout frontal cortex; a stark contrast to the most directly analogous studies with conventional paradigms 29,30,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results here showed that -while functional clusters of these processes are evident in the prefrontal and premotor cortices of marmosets engaged in natural vocal interactions -the organization is widely distributed throughout frontal cortex; a stark contrast to the most directly analogous studies with conventional paradigms 29,30,32 . We conjecture that the distributed functional organization during natural marmoset conversations was evident because the behavioral and cognitive processes that have traditionally been studied selectively through more targeted experimentation become more covaried in continuous, natural behaviors and, as such, rely on a more distributed computational ensemble coding strategy in primate frontal cortex 22 . Though admittedly limited in number, the few studies to directly compare neural responses in the primate brain between conventional and naturalistic paradigms have reported considerable differences 15,32 that may portend the need to evolve our conceptions of brain computations and behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation